A fotografia entre meios comunicativos - Oliveira, Tatiana Pontes de (2011)
The epistemological scope of this research is to investigate the supports of analogical photography and digital photography as communicative means. Based on the definition of communicative means composed of the materiality of language-producing signs by Lucrécia Ferrara, aspects that distinguish both supports have been identified and analyzed: discrete materialities of photographic images, different environments to process images (laboratory for analogical process and software for digital process), the relation of the photographer with production time, and how these aspects influence the creation process of the photographer and consequently make different communicative means appear. The research corpus or its empirical object is defined by comparison between works performed by three Brazilian photographers who use the two communicative means: Antonio Saggese, Cássio Vasconcelos and Cristiano Mascaro. The methodological strategy aims at analyzing and comparing the creation process of the chosen photographers in order to map the production course of their works and their choices for the use of each photographic means so as to verify the hypothesis for this research, which proposes discrete materialities, production environments and production time as determining elements for the photographer s stream of thoughts and for definition of discrete visualities. For that, the concept of creation network by Cecília Salles and that of bifurcations by Ilya Prigogine have been used. The work by Vilém Flusser has been fundamental for the development of this research, the idea to be highlighted being that of non-thing (information) to refer to technical images that have lost their bodiliness, and the definition of camera as a programmed apparatus for the analysis of the photographer s relation with the camera. Other thinkers of photographic images have been studied for the development of this research: Arlindo Machado, Boris Kossoy, Philippe Dubois, Walter Benjamin when they consider the photographic act photographer s role as an agent who transfigures the world and the relation of photography with reality. As far as specificities of images in the panorama of contemporaneous transformations, the references are the authors Edmond Couchot and François Soulages. This study made possible the understanding that contemporaneous photography lies in metalanguage from experimentation, which clearly places photography between the two communicative means: analogical and digital